(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
Through a spatial framing of learning and identity work in a youth gardening program in a Botanical Garden, I explore how youth come to see themselves in the program that they pass through and come to own through sustained engagement, next to how youth position themselves and others in such a place. Through stories of two youths’ forms of engagement with nature and reflections about gardening and science, I show in what ways such a spatial framing enhances our understanding of the role of botanical gardens as a science-rich informal educational venue and key resource for environmental education in a global world.